A remark on the excess of Hadamard matrices - Koukouvinos, Christos (Utilitas Mathematica, 1996)
In this note we improve the excess of Hadamard matrices of order 2(4k + 1)4k. We show that σ(2(4k + 1)4k) ≥ 43(4k + 1)24k-4 for each positive integer k.